Content analysis of web-based norovirus education materials targeting consumers who handle food: An assessment of alignment and readability. (July 2016) - Evans, Hillary; Chao, Morgan G.; Leone, Cortney M.; Finney, Michael; Fraser, Angela
Abstract: Human noroviruses sicken 19–21 million people in the U.S. each year, suggesting the need for education. The World Wide Web is an accessible source of information about how to prevent a norovirus infection but the accuracy and readability of information targeting consumers is unknown. The aim of the study was to evaluate the alignment and readability of web-based norovirus education materials targeting consumers using CDC evidence-based guidelines and Microsoft Word readability formulas. The search yielded 60 artifacts. Most did not address duration of handwashing (83%), use of hand sanitizers (83%), type of drying devices (92%), or avoidance of bare-hand contact with ready-to-eat foods (97%). Less than half (n = 29) recommended minimizing contact with sick persons. Two-thirds of the artifacts (n = 40) also did not mention the recommended concentration of sodium hypochlorite (bleach) solution to be used to disinfect surfaces contaminated with noroviruses. The mean Flesch Reading Ease score was 47.75 (score of >70 is easy to read), and the mean Flesch-Kincaid Grade Level was 10.36 so documents were written at a 10th grade level. The alignment and readability of web-based educational materials about noroviruses must be improved as knowledge is a prerequisite to application of behaviors that can prevent one from becoming infected with noroviruses. Highlights: Web-based norovirus educational materials not aligned with recommended prevention strategies. Norovirus prevention practices available through the Web were not well addressed. None of the analyzed artifacts addressed vomit and fecal matter clean up. Web-based norovirus materials are difficult to read.